PENGARUH HARGA, KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN KONSUMEN - Fatimatul Nur Wahidah; Anisa Nur Rokhmah; Amelia Rismawati; Kartika Sugiarti; Nawang Maulida Kuswanto; Yenni Kurnia Gusti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This research aims to find out how much influence price, service quality and promotion have on consumer satisfaction at Mie Gacoan Tamansiswa partially or simultaneously. The method used in this research is a quantitative method, where data collection uses a questionnaire. The sample in this study consisted of 101 respondents, where these consumers had purchased at Mie Gacoan Tamansiswa. The validity test shows that the statements in this research are valid, while the reliability test using Cronbach Alpha is declared reliable. This research uses multiple linear regression analysis. The results of the analysis show that: (1) price has a positive and significant effect on consumer satisfaction of 0.119. (2) service quality has a positive and significant effect on consumer satisfaction of 0.223. (3) Promotion has a positive and significant effect on consumer satisfaction of 0.289.